A polypropylene insulated medium voltage cable and its production process

By using graft-modified magnesium oxide embedded structure in polypropylene materials, the problem of insufficient mechanical properties and low temperature resistance of polypropylene insulating materials in cable applications is solved, and better dispersion and performance improvement is achieved.

CN119320532BActive Publication Date: 2025-03-28HUNAN HUALITONG CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411867984.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing polypropylene insulating materials have insufficient mechanical properties and low temperature resistance in cable applications, and the dispersion of nanoparticle modifiers is poor.

Method used

By coating maleic anhydride grafted olefin block copolymer with nano-scale magnesium oxide to form a rigid embedded structure and blending it with polypropylene material, the dispersion of nano-scale magnesium oxide is improved and the interface compatibility and stress transfer efficiency of polypropylene material are improved.

Benefits of technology

It significantly improves the mechanical properties and low temperature resistance of polypropylene materials, extends the service life of the cable, and improves the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a polypropylene insulated medium-voltage cable and a production process thereof. The method comprises the following steps: step 1, performing melt grafting reaction on maleic anhydride and olefin block copolymer to obtain a polymer matrix, and homogenizing the polymer matrix and magnesium oxide composite powder to obtain a modified copolymer; step 2, blending the modified copolymer with polypropylene resin to obtain a modified polypropylene resin, which is used as a PP insulation layer in the cable, and a conductor and a conductor shielding layer are subjected to non-crosslinked three-layer co-extrusion technology, and the polypropylene insulated medium-voltage cable is prepared after stepwise cooling; the modified polypropylene resin prepared by the process of the invention improves the stability of the polypropylene resin by uniformly dispersing composite magnesium oxide powder in the polypropylene resin, and the prepared polypropylene material has good shrinkage resistance at low temperature, and the composite magnesium oxide powder is dispersed in the polypropylene material as an inorganic filler to further improve the mechanical properties of the material, and the prepared cable has a long service life and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a polypropylene insulated medium-voltage cable and a production process thereof. Background Art

[0002] Driven by the national "dual carbon" goals, the construction of a new power system has brought unprecedented challenges and opportunities to the power cable industry. The byproducts produced by the cross-linking process of thermosetting cross-linked polyethylene (XLPE) materials will pollute the environment, and it is difficult to recycle after retirement, and it does not have the characteristics of green environmental protection. Polypropylene (PP) is a thermoplastic material with excellent electrical properties, high temperature resistance, simple processing technology, and recyclable after retirement. It is an environmentally friendly cable insulation material. Conventional PP materials cannot be directly used as cable insulation layers due to their defects such as high crystallinity and poor low-temperature toughness. PP materials need to be modified. At present, nanoparticle doping is one of the important means to improve the performance of PP materials.

[0003] Patent CN114292466A discloses a modified polypropylene insulation material for medium and low voltage power cables and a preparation method thereof. By simultaneously adopting three methods of elastomer blending modification, nano modification and grafting modification, thermoplastic elastomer, grafting material and nano oxide are introduced as polypropylene modifiers to improve the low temperature resistance and electrical properties of polypropylene materials; however, the molecular structure and intermolecular interactions in the blend will change, which increases the stereo configuration defects and is bound to reduce the electrical properties of the polypropylene insulation material.

[0004] Patent CN116462908A discloses a novel polypropylene-based cable material and its preparation method, wherein MgO nanoparticles are modified with a silane coupling agent, blended with molten polypropylene and an elastomer, and hot pressed to obtain a polypropylene-based cable material, thereby improving the mechanical toughness of polypropylene, inhibiting the injection and migration of space charges, and improving the dielectric properties of polypropylene cable materials. However, the binding ability of MgO to polypropylene is poor, which is more dependent on the degree of modification of MgO by the silane coupling agent, and the amount of silane coupling agent that can be added is limited, which has little effect on the performance improvement of polypropylene cable materials. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to improve the dispersibility of nanoparticle modifier in polypropylene material so as to improve the mechanical properties and low temperature resistance of polypropylene material in cable field application, and to provide a polypropylene insulated medium voltage cable and its production process.

[0006] The invention forms a rigid embedded structure by grafting olefin block copolymer with maleic anhydride and then coating with nano-scale magnesium oxide, and then blending with polypropylene material to disperse the nano-scale magnesium oxide in the polypropylene material. The copolymerization grafting modification improves the interface compatibility of the polypropylene material and improves the stress transfer efficiency. The elastomer and magnesium oxide filler reduce the shrinkage of the polypropylene material and improve the mechanical properties and low temperature resistance of the polypropylene material.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A production process for a polypropylene insulated medium voltage cable comprises the following steps:

[0009] Step 1: Perform melt grafting reaction on maleic anhydride, olefin block copolymer and dicumyl peroxide using a twin-screw extruder to obtain a polymer matrix, and homogenize the polymer matrix and magnesium oxide composite powder using a twin-screw extruder to obtain a modified copolymer.

[0010] Step 2: Blend the modified copolymer and polypropylene resin with a twin-screw extruder to obtain modified polypropylene resin, and use the obtained modified polypropylene resin as the PP insulation layer in the cable, and adopt non-crosslinked three-layer co-extrusion technology with the conductor and the conductor shielding layer, the temperature is 175-200°C, and segmented and step-by-step cooling is adopted to prepare a polypropylene insulated medium-voltage cable.

[0011] The magnesium oxide composite powder is prepared by mixing Mg-MOF-1 and Mg-MOF-2, grinding the mixture, and then heating the mixture to 550-600° C. in a muffle furnace and reacting the mixture for 2.5-3.5 hours.

[0012] The mixing mass ratio of Mg-MOF-1 and Mg-MOF-2 is 2.5-3:0.8-1.

[0013] Furthermore, in step 1, the mass ratio of maleic anhydride, olefin block copolymer and dicumyl peroxide is 1-2:10-15:0.15-0.3; and the mass ratio of the polymer matrix and magnesium oxide composite powder is 10-15:4-5.

[0014] Furthermore, in step 2, the mass ratio of the modified copolymer to the polypropylene resin is 2-3:15-18.

[0015] Further, Mg-MOF-1 is prepared by the following steps:

[0016] In a reaction kettle, phthalic acid is stirred and dissolved in N,N-dimethylformamide, boron nitride nanosheet powder is added, and ultrasonic dispersion is performed. Magnesium chloride hexahydrate is dissolved in N,N-dimethylformamide and then slowly added into the reaction kettle under stirring conditions. After mixing evenly, the temperature is raised to 130-145° C. and reacted for 22-26 hours. After cooling, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain Mg-MOF-1.

[0017] Furthermore, the mass ratio of phthalic acid, boron nitride nanosheet powder and magnesium chloride hexahydrate is 150-200:5-8g:200-300; the dosage ratio of phthalic acid to N,N-dimethylformamide is 3-4g:20-30mL; the dosage ratio of magnesium chloride hexahydrate to N,N-dimethylformamide is 2-3g:10-15mL.

[0018] Further, Mg-MOF-2 is prepared by the following steps:

[0019] In a reaction kettle, 2-methylimidazole was dissolved in N,N-dimethylformamide with stirring, magnesium chloride hexahydrate was dissolved in N,N-dimethylformamide and then slowly added into the reaction kettle under stirring conditions, mixed evenly and then heated to 130-145° C. and reacted for 22-26 hours. After cooling, the precipitate was collected by centrifugation, washed and vacuum dried to obtain Mg-MOF-2.

[0020] Furthermore, the mass ratio of 2-methylimidazole to magnesium chloride hexahydrate is 4-5:10-15; and the dosage ratio of magnesium chloride hexahydrate to N,N-dimethylformamide is 2-3g:10-15mL.

[0021] Furthermore, in step 1, the temperature of the melting zone in the twin-screw extruder is 140-180°C, the reaction zone is 190°C, the vacuum zone is 200°C, the mold temperature is 170-180°C, and the vacuum degree is 0.1 MPa; the homogenization temperature is 160-180°C.

[0022] Beneficial effects of the present invention:

[0023] The modified polypropylene resin prepared by the process of the invention is prepared by uniformly dispersing composite magnesium oxide powder in the polypropylene resin, the composite magnesium oxide powder is doped with boron nitride nano powder, the composite magnesium oxide powder can well maintain the stability of the polypropylene resin, the prepared polypropylene material has good shrinkage resistance at low temperature, the composite magnesium oxide powder is dispersed in the polypropylene material as an inorganic filler and also improves the mechanical properties of the material, and the prepared cable has a long service life and high stability.

[0024] The invention grafts maleic anhydride and olefin block copolymers and then coats them on the surface of composite magnesium oxide powder, and utilizes the good compatibility of the grafted polymer matrix in polypropylene resin to improve the dispersibility of the composite magnesium oxide powder in polypropylene resin.

[0025] The composite magnesium oxide powder prepared by the present invention is prepared by mixing and oxidizing two magnesium metal organic frameworks with special morphologies. Boron nitride nanosheet powder is added during the hydrothermal generation of the flaky magnesium metal organic framework, so that the boron nitride nanosheet powder is intercalated and combined with the flaky magnesium metal organic framework, and the degree of combination is strong, which further improves the strength of the composite magnesium oxide powder after the magnesium metal organic framework is oxidized, thereby improving the performance improvement ability of the composite magnesium oxide powder on the polypropylene resin. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1: A production process of a polypropylene insulated medium voltage cable, comprising the following steps:

[0028] Step 1: In a reactor, 150g of phthalic acid was stirred and dissolved in 1L of N,N-dimethylformamide, 5g of boron nitride nanosheet powder was added, and ultrasonic dispersion was performed for 20min. 200g of magnesium chloride hexahydrate was dissolved in 1L of N,N-dimethylformamide and then slowly added to the reactor under stirring conditions. After mixing evenly, the temperature was raised to 130°C and reacted for 22h. After cooling, the precipitate was collected by centrifugation and washed with N,N-dimethylformamide and methanol in turn. Mg-MOF-1 was obtained by vacuum drying at 55°C for 12h.

[0029] Step 2: In a reaction kettle, 80 g of 2-methylimidazole was dissolved in 1 L of N, N-dimethylformamide, 200 g of magnesium chloride hexahydrate was dissolved in 1 L of N, N-dimethylformamide, and then slowly added to the reaction kettle under stirring conditions. After mixing evenly, the temperature was raised to 130°C for reaction for 22 hours. After cooling, the precipitate was collected by centrifugation, washed with N, N-dimethylformamide and methanol in turn, and dried under vacuum at 55°C for 12 hours to obtain Mg-MOF-2.

[0030] Step 3: Mg-MOF-1 and Mg-MOF-2 were mixed in a mass ratio of 2.5:0.8 and ground for 1 min. Then, the mixture was transferred to a muffle furnace and heated to 550° C. for reaction for 2.5 h to form a magnesium oxide composite powder.

[0031] Step 4: melt graft reaction of 10 g of maleic anhydride, 100 g of olefin block copolymer and 1.5 g of diisopropylbenzene peroxide by a twin-screw extruder, the temperature of the melting zone is 140°C, the reaction zone is 190°C, the vacuum zone is 200°C, the mold temperature is 170°C, the vacuum degree is 0.1 MPa, to obtain a polymer matrix, 100 g of the polymer matrix and 40 g of magnesium oxide composite powder are homogenized by a twin-screw extruder, the homogenization temperature is 160°C, to obtain a modified copolymer.

[0032] Step 5: Blend 100 g of the modified copolymer with 750 g of polypropylene resin using a twin-screw extruder to obtain a modified polypropylene resin. Use the obtained modified polypropylene resin as the PP insulation layer in the cable, and use a non-cross-linked three-layer co-extrusion technology with the conductor and the conductor shielding layer at a temperature of 175°C. Use segmented and step-by-step cooling to prepare a polypropylene insulated medium-voltage cable.

[0033] Example 2: In a reactor, 180 g of phthalic acid was stirred and dissolved in 1.2 L of N, N-dimethylformamide, 6.5 g of boron nitride nanosheet powder was added, and ultrasonic dispersion was performed for 25 min. 250 g of magnesium chloride hexahydrate was dissolved in 1.2 L of N, N-dimethylformamide and then slowly added to the reactor under stirring conditions. After mixing evenly, the temperature was raised to 140°C and reacted for 24 h. After cooling, the precipitate was collected by centrifugation, washed with N, N-dimethylformamide and methanol in turn, and dried under vacuum at 60°C for 14 h to obtain Mg-MOF-1.

[0034] Step 2: In a reaction kettle, 90 g of 2-methylimidazole was dissolved in 1.2 L of N, N-dimethylformamide, 250 g of magnesium chloride hexahydrate was dissolved in 1.2 L of N, N-dimethylformamide, and then slowly added to the reaction kettle under stirring conditions. After mixing evenly, the temperature was raised to 140°C and reacted for 24 hours. After cooling, the precipitate was collected by centrifugation, washed with N, N-dimethylformamide and methanol in turn, and dried under vacuum at 60°C for 14 hours to obtain Mg-MOF-2.

[0035] Step 3: Mg-MOF-1 and Mg-MOF-2 were mixed in a mass ratio of 2.8:0.9 and ground for 1.5 min. Then, the mixture was transferred to a muffle furnace and heated to 580° C. for reaction for 3 h to form a magnesium oxide composite powder.

[0036] Step 4: 15 g of maleic anhydride, 125 g of olefin block copolymer and 2.2 g of diisopropylbenzene peroxide are subjected to melt grafting reaction using a twin-screw extruder. The temperature of the melting zone is 160°C, the reaction zone is 190°C, the vacuum zone is 200°C, the mold temperature is 175°C, and the vacuum degree is 0.1 MPa to obtain a polymer matrix. 125 g of the polymer matrix and 45 g of magnesium oxide composite powder are homogenized using a twin-screw extruder at a homogenization temperature of 170°C to obtain a modified copolymer.

[0037] Step 5: Blend 125 g of the modified copolymer with 825 g of polypropylene resin using a twin-screw extruder to obtain a modified polypropylene resin. Use the obtained modified polypropylene resin as the PP insulation layer in the cable, and use a non-cross-linked three-layer co-extrusion technology with the conductor and the conductor shielding layer at a temperature of 190°C. Use segmented and step-by-step cooling to prepare a polypropylene insulated medium-voltage cable.

[0038] Embodiment 3: A production process of a polypropylene insulated medium voltage cable, comprising the following steps:

[0039] Step 1: In a reactor, 200g of phthalic acid was stirred and dissolved in 1.5L of N,N-dimethylformamide, 8g of boron nitride nanosheet powder was added, and ultrasonic dispersion was performed for 30min. 300g of magnesium chloride hexahydrate was dissolved in 1.5L of N,N-dimethylformamide and then slowly added to the reactor under stirring conditions. After mixing evenly, the temperature was raised to 145°C and reacted for 26h. After cooling, the precipitate was collected by centrifugation and washed with N,N-dimethylformamide and methanol in turn. Mg-MOF-1 was obtained by vacuum drying at 65°C for 16h.

[0040] Mg-MOF whose ligand is phthalic acid is generated in situ by hydrothermal reaction. The morphology of the synthesized Mg-MOF is flaky. Boron nitride nanosheet powder is added during the synthesis process so that the boron nitride nanosheet powder is loaded in the gaps of the Mg-MOF sheet structure.

[0041] Step 2: In a reaction kettle, 100 g of 2-methylimidazole was dissolved in 1.5 L of N, N-dimethylformamide, and 300 g of magnesium chloride hexahydrate was dissolved in 1.5 L of N, N-dimethylformamide, and then slowly added to the reaction kettle under stirring conditions. After mixing evenly, the temperature was raised to 145°C for reaction for 26 hours. After cooling, the precipitate was collected by centrifugation, and washed with N, N-dimethylformamide and methanol in turn. It was dried under vacuum at 65°C for 16 hours to obtain Mg-MOF-2.

[0042] Mg-MOF with 2-methylimidazole as ligand is generated in situ by hydrothermal reaction. The morphology of the synthesized Mg-MOF is an octahedral structure. The octahedral magnesium oxide has abundant surface defect reaction sites.

[0043] Step 3: Mg-MOF-1 and Mg-MOF-2 were mixed in a mass ratio of 3:1 and ground for 2 minutes, then transferred to a muffle furnace and heated to 600° C. for reaction for 3.5 hours to form a magnesium oxide composite powder.

[0044] Mg-MOF-1 and Mg-MOF-2 are ground and crushed to make them evenly mixed, and then heated and oxidized to oxidize Mg-MOF-1 and Mg-MOF-2 into magnesium oxide powder with similar structure to the original one. The formed magnesium oxide composite powder retains the lamellar structure of Mg-MOF-1 and the octahedral structure of Mg-MOF-2. During the oxidation process, Mg-MOF-1 and Mg-MOF-2 will randomly compound. The formed lamellar and octahedral composite structures are beneficial to maintain the mechanical strength of polypropylene resin, and synergize with the boron nitride in the flaky magnesium oxide to improve the shrinkage resistance of polypropylene resin at low temperature.

[0045] Step 4: 20 g of maleic anhydride, 150 g of olefin block copolymer and 3 g of diisopropylbenzene peroxide are subjected to melt grafting reaction using a twin-screw extruder. The temperature of the melting zone is 180°C, the reaction zone is 190°C, the vacuum zone is 200°C, the mold temperature is 180°C, and the vacuum degree is 0.1 MPa to obtain a polymer matrix. 150 g of the polymer matrix and 50 g of magnesium oxide composite powder are homogenized using a twin-screw extruder at a homogenization temperature of 180°C to obtain a modified copolymer.

[0046] Maleic anhydride and olefin block copolymers have good compatibility with polypropylene resin after grafting. The magnesium oxide composite powder is coated with a polymer matrix, and the composite magnesium oxide powder is uniformly compounded with the polymer matrix by utilizing the abundant defect reaction sites on the surface of octahedral magnesium oxide, thereby improving the dispersibility of the magnesium oxide composite powder in the polypropylene resin and better improving the low-temperature shrinkage resistance and mechanical strength of the polypropylene resin.

[0047] Step 5: Blend 150 g of the modified copolymer with 900 g of polypropylene resin using a twin-screw extruder to obtain a modified polypropylene resin. Use the obtained modified polypropylene resin as the PP insulation layer in the cable, and use a non-cross-linked three-layer co-extrusion technology with the conductor and the conductor shielding layer at a temperature of 200°C. Use segmented and stepwise cooling to prepare a polypropylene insulated medium-voltage cable.

[0048] In the examples, the specific method and parameters for producing the cable by three-layer co-extrusion technology of modified polypropylene, conductor and conductor shielding layer adopt the technology known to those skilled in the art.

[0049] Comparative Example 1: The difference from Example 1 is that magnesium oxide composite powder is replaced by magnesium oxide nanoparticles.

[0050] Comparative Example 2: The difference from Example 1 is that Mg-MOF-2 is not added in step three.

[0051] Comparative Example 3: The difference from Example 1 is that the magnesium oxide composite powder is directly mixed with the polypropylene resin to obtain the modified polypropylene resin.

[0052] The sources of some reagents in the embodiments and comparative examples are as follows:

[0053] Phthalic acid, N,N-dimethylformamide, 2-methylimidazole, maleic anhydride, and dicumyl peroxide were purchased from Sigma-Aldrich.

[0054] Magnesium chloride hexahydrate was purchased from MacLean Reagent Co., Ltd.

[0055] Polypropylene resin was purchased from Beijing Zhonglai Chemical Co., Ltd.

[0056] The olefin block copolymer is selected from Dow olefin block copolymer of the United States, brand 9100, purchased from Dongguan Bailing New Materials Co., Ltd.

[0057] Thermal aging treatment: XLPE, PP-1# and PP-2# samples were aged in a constant temperature aging oven for 21 days at a temperature of 135°C. After the aging test, the samples were taken out of the oven and placed in a cool place for 16 hours.

[0058] The polypropylene insulated medium voltage cables prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were made into 2×2×2 mm samples for mechanical properties and thermal aging properties at low temperature. The thermal aging properties test method is as follows: the samples are placed in a xenon lamp aging test box in an air atmosphere for accelerated aging for 14 days, the wavelength of the xenon lamp is 280-800 nm, and the irradiation intensity is 550 W / m 2 According to the standard GB / T1043.1-2008, the notched impact strength of the sample before and after aging was tested; according to the standard GB / T1043.1-2008, the notched impact strength of the sample at 0°C was measured; according to the standard GB / T2951.13-2008, the shrinkage rate of the sample at 0°C was tested, and the results are shown in Table 1:

[0059]

[0060] It can be seen from Table 1 that the cables prepared in Examples 1 to 3 have good mechanical properties, and the mechanical properties are less reduced at a low temperature of 0°C, and the shrinkage rate at 0°C is low, and they have good mechanical properties and resistance to low-temperature shrinkage;

[0061] In Comparative Example 1, due to the use of magnesium oxide nanoparticles, the mixing uniformity with the polymer matrix is ​​low, and the magnesium oxide nanoparticles have the same morphology, so the reinforcement performance of the polypropylene cable is limited, and the mechanical properties of the prepared polypropylene cable are lower than those of Examples 1 to 3;

[0062] Since no Mg-MOF-2 with an octahedral structure was added to Comparative Example 2, the mixing uniformity of the magnesium oxide composite powder and the polymer matrix was low, and only the magnesium oxide composite powder with a lamellar structure had a small degree of reduction in the shrinkage of the polypropylene cable. Therefore, the mechanical strength and shrinkage of Comparative Example 2 were inferior to those of Examples 1 to 3.

[0063] In Comparative Example 3, since the magnesium oxide composite powder is directly mixed with the polypropylene resin, the magnesium oxide composite powder agglomerates, has poor dispersion, and has a low degree of modification on the polypropylene resin.

[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for a polypropylene insulated medium voltage cable, characterized in that: The steps include: Step 1: melt grafting maleic anhydride, olefin block copolymer and dicumyl peroxide using a twin-screw extruder to obtain a polymer matrix, and homogenizing the polymer matrix and magnesium oxide composite powder using a twin-screw extruder to obtain a modified copolymer; Step 2: Blending the modified copolymer with the polypropylene resin by a twin-screw extruder to obtain a modified polypropylene resin, using the obtained modified polypropylene resin as the PP insulation layer in the cable, and adopting a non-crosslinked three-layer co-extrusion technology with the conductor and the conductor shielding layer, the temperature is 175-200° C., and step-by-step cooling is adopted to prepare a polypropylene insulated medium-voltage cable; The magnesium oxide composite powder is prepared by mixing Mg-MOF-1 and Mg-MOF-2, grinding them, and then heating them to 550-600° C. in a muffle furnace and reacting them for 2.5-3.5 hours; The mixing mass ratio of Mg-MOF-1 and Mg-MOF-2 is 2.5-3:0.8-1; In step 1, the mass ratio of maleic anhydride, olefin block copolymer and dicumyl peroxide is 1-2:10-15:0.15-0.3; the mass ratio of the polymer matrix and magnesium oxide composite powder is 10-15:4-5; The Mg-MOF-1 is prepared by the following steps: In a reaction kettle, phthalic acid is stirred and dissolved in N,N-dimethylformamide, boron nitride nanosheet powder is added, and ultrasonic dispersion is performed. Magnesium chloride hexahydrate is dissolved in N,N-dimethylformamide and then slowly added into the reaction kettle under stirring conditions. After mixing evenly, the temperature is raised to 130-145° C. and reacted for 22-26 hours. After cooling, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain Mg-MOF-1. The Mg-MOF-2 is prepared by the following steps: In a reaction kettle, 2-methylimidazole was dissolved in N,N-dimethylformamide with stirring, magnesium chloride hexahydrate was dissolved in N,N-dimethylformamide and then slowly added into the reaction kettle under stirring conditions, mixed evenly and then heated to 130-145° C. and reacted for 22-26 hours. After cooling, the precipitate was collected by centrifugation, washed and vacuum dried to obtain Mg-MOF-2.

2. The production process of a polypropylene insulated medium voltage cable according to claim 1, characterized in that: The mass ratio of the modified copolymer to the polypropylene resin in step 2 is 2-3:15-18.

3. The production process of a polypropylene insulated medium voltage cable according to claim 1, characterized in that: The mass ratio of the phthalic acid, boron nitride nanosheet powder and magnesium chloride hexahydrate is 150-200:5-8:200-300; the dosage ratio of the phthalic acid to N,N-dimethylformamide is 3-4g:20-30mL; the dosage ratio of the magnesium chloride hexahydrate to N,N-dimethylformamide is 2-3g:10-15mL.

4. The production process of a polypropylene insulated medium voltage cable according to claim 1, characterized in that: The mass ratio of the 2-methylimidazole to magnesium chloride hexahydrate is 4-5:10-15; the dosage ratio of magnesium chloride hexahydrate to N,N-dimethylformamide is 2-3g:10-15mL.

5. The production process of a polypropylene insulated medium voltage cable according to claim 1, characterized in that: In step 1, the temperature of the melting zone in the twin-screw extruder is 140-180°C, the reaction zone is 190°C, the vacuum zone is 200°C, the mold temperature is 170-180°C, and the vacuum degree is 0.1MPa; the homogenization temperature is 160-180°C.

6. A polypropylene insulated medium voltage cable, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Modified cable protection pipe material and preparation method thereof

    CN103724812A

  • Preparation method of thermal conductive and insulation material of high power LED substrate

    CN105038081A